Cybersecurity from International Perspectives: The Cases of the UN and EU Initiatives - Önder Kutlu (Proceeding International Conference Restructuring and Transforming Law, 2026)
Cybersecurity as a global phenomenon has been on the agendas of international organisations for not only making policies but also keeping and maintaining tranquillity of nations. The nature of the subject imposes joint efforts of actors and defining policies at international level. The paper deploys the UN and the EU cases to shed light on their involvements in cybersecurity in terms of history, principles, means and mechanisms. The cases provide invaluable lessons for nation states and international organisations as the subject area has witnessed growing concerns with the advancements in technology as well as criminalisation of the area by mischievous behaviours of the criminal actors.With the increase of awareness in the public about security concerns and the devastating effects of cybercrime, policy makers at national and international levels intend to pay attention to the issue. Hence, the consequences have wider implications in the public and in every actor in the society. Therefore, joint efforts should best be orchestrated by deliberate activities of international organisations. The two cases have their own histories and priorities. In addition, their special mechanisms and means are forward oriented and could guide member states in their activities.This paper examines cybersecurity with its international dimension and finds that these unique cases set a blueprint for other organisations and nations to follow. The UN, for this purpose, has adopted the Sustainable Development Goals (SDGs) in respect to cybersecurity applications inter alia other purposes. This has alleviated the reception of the problem as sustaining the development of goals which are generally accepted proposals for the entire humanity, while the EU has concrete and effectful policies and organs to facilitate cybersecurity arrangements. The cases hint that development of cybersecurity studies influences general atmosphere in which every public policy actor (re)acts. So, without international level activities and provisions, national endeavours would have limited impacts.